Paget’s disease of the breast (a review of literature) - E. A. Nikitina; M. I. Nechushkin; A. V. Trigolosov; Ya. V. Vishnevskaya (Опухоли женской репродуктивной системы, 2017)
Paget’s disease (PD) of the nipple is a rare form of breast cancer, characterized by erythema, an scaling of the skin and eczematous changes of the nipple-areolar complex. Despite a significant increase in newly detected cases of breast cancer, PD is accounting for 0.5–5.0 % of all breast tumors in the world. In female patients with PD ages range from 24 to 90 years (average age range 50–60 years), predominantly menopausal age in 70 % of cases. But cases of PD in young person were reported.Currently, the relevance of the PD of the nipple is preserved. There are different methods of treatment, but we haven’t specific international recommendations for treatment PD in surgery, irradiation and chemotherapy or target therapy. There are small numbers of randomized studies of PD. The use of modern methods of instrumental and molecular diagnostics can help designed algorithm the treatment of PD.In this literature review the etiology, clinical features and current approaches to diagnosis and possible treatment of PD of the nipple.